INVESTIGATING THE IMPLEMENTATION OF COLLABORATIVE STRATEGIC READING (CSR) IN EFL CONTEXT: PROFICIENCY AND PERSPECTIVES - Herda, Rozanah Katrina; Setiawan, Teguh; Principe, Regine Aguilar (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
The students are mostly unmotivated in the EFL reading classrooms since they have problems reading English texts. They feel stressed as they consider themselves alone, readers who cannot understand the text content well. This mixed-method study aimed to (1) investigate the significant difference between the mean scores of the pretest and the post-test in reading using Collaborative Strategic Reading (CSR) and (2) describe the students' reflections using CSR in the reading classroom. The data were collected by using a pretest-posttest and students' reflection sheets. The participants were 32 students from a private university in Indonesia. The pretest and post-test results indicated that CSR significantly improved students' reading skills in collaborative classrooms. The written reflections showed students were highly motivated to join collaborative reading, as the strategies were beneficial for improving their vocabulary, reading understanding, and critical thinking. This study greatly influences improving students' reading proficiency and social skills.